2022
DOI: 10.1109/jphotov.2021.3129073
|View full text |Cite
|
Sign up to set email alerts
|

TOPCon Silicon Solar Cells With Selectively Doped PECVD Layers Realized by Inkjet-Printing of Phosphorus Dopant Sources

Abstract: In this article, we evaluate an industrially relevant alternative for the formation of selectively doped n-type tunnel oxide passivating contacts (n-TOPCon) by means of inkjet-printing with the goal to provide a low contact resistance as well as fulfilling the requirements for screen-printing metallization. It is shown that inkjet-printing of phosphorus dopant sources for thick TOPCon layers deposited by plasma-enhanced chemical vapor deposition provides excellent surface passivation with the implied open-circ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Additionally to the above-mentioned problems, Potential-Induced Degradation (PID), Light-Induced Degradation (LID), and general degradation are indeed crucial concerns in the realm of PV technology, especially with the advent of modern advancements like the half-cut Passivated Emitter Rear Cell (PERC) [87,88] or Top Contact (TopCon cells) [89,90]. It may take a long time to detect the PID through traditional data analysis methods, resulting in an undetected energy loss [91].…”
Section: Typical Maintenance Issuesmentioning
confidence: 99%
“…Additionally to the above-mentioned problems, Potential-Induced Degradation (PID), Light-Induced Degradation (LID), and general degradation are indeed crucial concerns in the realm of PV technology, especially with the advent of modern advancements like the half-cut Passivated Emitter Rear Cell (PERC) [87,88] or Top Contact (TopCon cells) [89,90]. It may take a long time to detect the PID through traditional data analysis methods, resulting in an undetected energy loss [91].…”
Section: Typical Maintenance Issuesmentioning
confidence: 99%
“…In this study, phosphorus (P) and boron (B) dopant-source inks were used, which find applications in high-efficiency silicon solar cells [ 14 ], thin-film transistors [ 15 ], etc. Promising results for local inkjet printing with dopant-source inks incorporating tunnel oxide passivating contact (TOPCon) technology for Si solar cells have been reported [ 16 , 17 ]. Successful local passivating contacts on SiOx/Poly-Si have also been developed using P and B dopant-source inks [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to achieving excellent passivation, the most unique advantage of this approach is the capability for forming localized poly-Si passivating contacts without costly masking processes. Recently, by printing phosphorus dopant lines with a width of around 300 μm underneath the screen-printed metal fingers, Kiaee et al applied inkjet-printing technology to selectively dope n-type TOPCon layers on industrial solar cells for the first time, with a promising conversion efficiency of 22.0% . Their achievements demonstrated that inkjet-printed doping can be an effective method to fabricate poly-Si passivating contacts.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, more work is required to optimize the hightemperature annealing processes, narrow the printed line width, and eliminate the outgassing of dopants from the printed region, 31 in order to achieve higher-efficiency silicon solar cells. In this work, we employed a FUJIFILM Material Printer DMP-2850 to fabricate n-type poly-Si passivating contacts.…”
Section: Introductionmentioning
confidence: 99%